The role and competences of the Supreme Bioethics Committee and local bioethics committees in the context of protecting the rights of clinical trial participants in Poland: Ethics and participants' rights in clinical trials - Molenda, Michał; Busławski, Adam; Krówczyńska, Dorota; Zierkiewicz, Dorota; Manulik, Stanisław; Pobrotyn, Piotr; Głowacka, Mariola (Journal of Education, Health and Sport, 2025)
The introduction in Poland of a centralized system for the ethical evaluation of clinical trials of medicinal products, under which the Supreme Bioethics Committee (NKB) was established, is a response to the need to harmonize procedures, increase transparency, and strengthen the protection of trial participants. The purpose of this article is to discuss the tasks and competences of the NKB and local bioethics committees (LKB) in the light of the applicable legal provisions, in particular the Act of March 9, 2023, on clinical trials of medicinal products and implementing regulations. The authors analyze the structure, composition, and mode of operation of both types of committees, as well as the principles of cooperation and supervision between them. Particular attention is paid to the ethical review procedure, the role of patient representatives, the prevention of conflicts of interest, and mechanisms for protecting the rights of participants. The article also points out how the new regulations strengthen the transparency, quality, and uniformity of bioethical standards in clinical trials conducted in the Republic of Poland. The article is of a review and analytical nature and refers to current legal sources, institutional documents, and practices implemented by the NKB and superior entities such as the Medical Research Agency (ABM). The tabular summaries and descriptions of institutional relationships presented are intended to facilitate understanding of the complex system of ethical supervision in clinical trials, in particular from the perspective of participant protection as a core value.